I got a feeling: Exploring precognitions in elite golfers - Pates, J. (Journal of Athletic Enhancement, 2020)
The purpose of this study was to examine the subjective experience of a form of intuition called precognition (the ability to sense the future), purported by four elite golfers playing on the PGA European Golf Tour. The participants were selected for this study on the basis of their reported experiences of precognitions during their playing careers. An open-ended, semi-structured phenomenological interview was used to gain a description of their experiences. A Thematic analysis of transcripts describing their experiences resulted in the identification of five major themes associated with intuition in this context. These were `clutch situations,` emotionally arousing stimuli,` `pre-feeling,` `self-talk,` and `prospective imagery`. The results of this study suggest precognitions manifest in clutch situations and pre-empt performance excellence. The findings could provide valuable insight for researchers and practitioners interested in the phenomena of intuition and its role in optimizing performance.